A model of the topology of the bank-firm credit network and its role as channel of contagion - Thomas Lux (Kiel Institute for the World Economy (IfW), 2014)
This paper proposes a stochastic model of a bipartite credit network between banks and the non-bank corporate sector that encapsulates basic stylized facts fond in comprehensive data sets for bank-firm loans for a number of countries. When performing computational experiment with this mode, we find that is shows a pronounced non-linear behavior under shock: The default of a single unit will mostly have practically no know-on effects, but might lead to an almost full-scale collapse of the entire system in a certain number of cases. The dependency of the overall outcome on firm characteristics like size or number of loans seems fuzzy. Distinguishing between contagion due to interbank credit and due to joint exposures to counterparty risk via loans to firms, the later channel appears more important for contagious spread of defaults.
Keywords: D85; G21; D83; 330; Credit Network; Contagion; Interbank Network